Neural cell adhesion molecule 180 participates in proliferation of melanoma cells through interaction with β-catenin. - Wong, Jack Jing Lin. (2009)
Neural cell adhesion molecule (NCAM), a member of the immunoglobulin superfamily, is expressed not only in the neuronal system but also in various types of cancer including melanoma. Very often, its expression in cancer is highly dysregulated. NCAM performs diverse functions such as classical functions of cell adhesion and cellular signaling which have already been well characterized in the neuronal system, but its role in melanoma progression still remains elusive. In this study, we demonstrated that one of NCAM’s three major isoforms, NCAM 180, is capable of upregulating proliferation when over-expressed in B16F0 melanoma cells. This is in contrast to a key transcription transactivator, β-catenin’s over-expression in B16F0 cells. We further demonstrated through co-immunoprecipitation that NCAM is capable of interacting with β-catenin, with NCAM 180 over-expressing cells being able to pull down more β-catenin. Immunofluorescene study had also demonstrated the colocalization of NCAM and β-catenin. Subcellular fractionation studies have also shown that over-expression of NCAM 180 significantly reduces β-catenin nuclear localization. Finally, the over-expression of β-catenin effectively abolished NCAM 180 mediated proliferation in NCAM 180 over-expressing B16F0 cells.